Incarceration history and risk of HIV and hepatitis C virus acquisition among people who inject drugs: A systematic review and meta-analysis - Stone, Jack; Fraser, Hannah; Lim, Aaron G; Walker, Josephine G; Ward, Zoe; MacGregor, Louis; Trickey, Adam; Abbott, Sam; Strathdee, Steffanie A; Abramovitz, Daniela; Maher, Lisa; Iversen, Jenny; et al. (The Lancet, 2022)
This article was published in the The Lancet Infectious Diseases [© 2018 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license.] and the definite version is available at: https://doi.org/10.1016/S1473-3099(18)30469-9 The Journal's website is at: https://www.thelancet.com/journals/laninf/article/PIIS1473-3099(18)30469-9/fulltext